1985
DOI: 10.1007/bf00583277
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation by glucagon and PTH of Ca and Mg reabsorption in the superficial distal tubule of the rat kidney

Abstract: The effects of glucagon and PTH on electrolyte reabsorption in the distal tubule were investigated in rats deprived of vasopressin, calcitonin, PTH, and glucagon. Micropunctures of distal tubule, at a late and an early site of a same nephron, have been performed in 23 rats, nine control, seven infused with glucagon (5 ng X min-1 X 100 g-1 b.w.) and seven with PTH (5 mU X min-1 X 100 g-1 b.w.). The Ca and Mg reabsorptive capacity of the distal segment was increased by glucagon and by PTH. Moreover, fractional N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

1986
1986
2007
2007

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 20 publications
1
26
0
Order By: Relevance
“…an increase in the lumen-positive potential), thereby increasing magnesium absorption via the paracellular pathway [6]. In the distal tubule, where transcellular magnesium absorption occurs [6], micropuncture studies have demonstrated that PTH also significantly increases magnesium transport [7].…”
Section: Introductionmentioning
confidence: 99%
“…an increase in the lumen-positive potential), thereby increasing magnesium absorption via the paracellular pathway [6]. In the distal tubule, where transcellular magnesium absorption occurs [6], micropuncture studies have demonstrated that PTH also significantly increases magnesium transport [7].…”
Section: Introductionmentioning
confidence: 99%
“…Free access to distilled water was available until anesthesia. The animals were prepared in order to reduce the plasma concentration of calcitonin, PTH, and glucagon (6)(7)(8)(9)(10)(11). They are called hormone-deprived animals throughout this paper.…”
Section: Methodsmentioning
confidence: 99%
“…The response ofthe collecting ducts was evaluated by the changes in urine flow. Calcitonin, parathyroid hormone (PTH), and glucagon may act on Mg2+ reabsorption in the distal tubule (7,8) and the thick ascending limb (9,10), and calcitonin may act in the same way as [Arg8]vasopressin on the permeability of the cortical collecting duct to water (11,12). To avoid undesirable interference from these hormones, the experiments were performed with hormone-deprived rats (4); i.e., Brattleboro D. I. rats (lacking [Arg8]vasopressin) that were acutely thyroparathyroidectomized (thus suppressing calcitonin and PTH levels) and given somatostatin to inhibit glucagon secretion (6)(7)(8)(9)(10)(11).…”
mentioning
confidence: 99%
“…There is already evidence (Quamme, 1982) that hypercalcaemia reduces reabsorption of both calcium and magnesium at this site and that here is interaction between the reabsorptive processes for the two cations (Quamme & Dirks, 1980). Glucagon and PTH stimulate reabsorption of both cations (Bailly, Roinel & Amiel, 1985) as does calcitonin (Di Stefano, Elalouf, Garel & de Rouffignac, 1985). The mechanism of magnesium reabsorption by the loop of Henle is not known although it appears to be related to sodium chloride transport, possibly via changes in intratubular potential difference (Quamme, 1986).…”
Section: Discussionmentioning
confidence: 99%